TRIF licenses caspase-11-dependent NLRP3 inflammasome activation by gram-negative bacteria - Rathinam, Vijay A K; Vanaja, Sivapriya Kailasan; Waggoner, Lisa; Sokolovska, Anna; Becker, Christine; Stuart, Lynda M; Leong, John M; Fitzgerald, Katherine A (Cell, 2012)
Systemic infections with Gram-negative bacteria are characterized by high mortality rates due to the "sepsis syndrome," a widespread and uncontrolled inflammatory response. Though it is well recognized that the immune response during Gram-negative bacterial infection is initiated after the recognition of endotoxin by Toll-like receptor 4, the molecular mechanisms underlying the detrimental inflammatory response during Gram-negative bacteremia remain poorly defined. Here, we identify a TRIF pathway that licenses NLRP3 inflammasome activation by all Gram-negative bacteria. By engaging TRIF, Gram-negative bacteria activate caspase-11. TRIF activates caspase-11 via type I IFN signaling, an event that is both necessary and sufficient for caspase-11 induction and autoactivation. Caspase-11 subsequently synergizes with the assembled NLRP3 inflammasome to regulate caspase-1 activation and leads to caspase-1-independent cell death. These events occur specifically during infection with Gram-negative, but not Gram-positive, bacteria. The identification of TRIF as a regulator of caspase-11 underscores the importance of TLRs as master regulators of inflammasomes during Gram-negative bacterial infection.